Inonotus hispidus (Bull.) P. Karst from the Inner Western Anatolia part of Türkiye with a molecular analysis, phenotypic characters study, genus of host determination, and geo-hydrographic distribution factors analysis - Ahmed Badri Abed; Kaan Hürkan; Safiye Elif Korcan; Arzu Ünal (Bulletin of the National Research Centre)
Abstract Background Inonotus hispidus is a valuable medicinal fungus that is frequently used in folk medicine, particularly in China, to cure various illnesses. It also has antioxidant, anticancer, and immunomodulatory properties. Few studies have been conducted to determine its genomic sequence and potential for secondary metabolite production. With this work, we hope to contribute to the scientific knowledge of I. hispidus. Results In this study, molecular analysis, phenotypic character study, and metabolite research were performed for a macrofungus isolated in Uşak province, Türkiye. A survey was conducted to determine the genus of the host. The macrofungus was recognised as I. hispidus based on the morphological features of the fruiting body and the Internal Transcribed Spacer regions sequence alignment, which revealed 99.22% similarity to I. hispidus (GenBank accession FR686562.1). Sequences of the ITS region, which were used to construct a maximum likelihood tree, revealed a well-supported monophyletic clade comprising all I. hispidus isolates. The phylogeny clearly distinguished I. hispidus from closely related taxa such as I. rickii and I. dryophilus, while confirming its separation from other genera including Sanghuangporus and Tropicoporus. The study revealed a new record for the genus Inonotus and the species I. hispidus in the Inner Western Anatolia part of Türkiye. As well, the survey study pointed to Morus spp. as the only host. A metabolite study indicated that the fungus contained 16 polyphenols with a highly medicinal value, and ethyl acetate appeared to possess better extraction potency in the extraction of phenolics from I. hispidus. Conclusions The presence of 17 variable medicinal ingredients in one fungus species grown solely on mulberry trees refers to the importance of this host in providing essential ingredients for I. hispidus. The study included an updated analysis of the morphological characteristics, essential polyphenols, and preferred host. Geographic, hydrographic, and climatic factors impacting I. hispidus distribution are also included. The study discussed significant data that deepens our knowledge of this medicinal macrofungus.